PROBLEM MANAJEMEN LINGKUNGAN DAN ISU INDUSTRIALISASI - - M. Nasir; - Fatkhurohman; Agus Muqorobin (Universitas Muhammadiyah Semarang, 2011)
Environmental values play a primary role in pro-environmental behaviour: values affect people’sbeliefs, which then have influences on personal norms that lead to consumers’ pro-environmental behaviours.So, if the market for environmentally sustainable products is to become mainstream, it is important to look atwhat factors influence the consumer’s selection process. In current green marketing, branding is underutilised.The affective use of branding in selling green products should be part of marketing strategies.The effect of emotion on influencing decisions, attitude formation and memory retrieval, and the rolethat emotions play in consumer response to brands, should be taken into account. Consumers would be morelikely to choose brands which they knew were manufactured by companies whose products and processes weremore environmentally friendly. Consumers also feel good about buying brands which are less damaging to theenvironment. The cognitive-based marketing communication that is mostly used to sell environmentally friendlyproducts is useful only in some of the ways consumers form product attitudes, thus limiting their appeal.